2021
DOI: 10.1038/s41598-021-97235-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased NKX6.1 expression and decreased ARX expression in alpha cells accompany reduced beta-cell volume in human subjects

Abstract: Pancreatic islet cells have plasticity, such as the abilities to dedifferentiate and transdifferentiate. Islet cell conversion to other characteristic cell is largely determined by transcription factors, but significance of expression patterns of these transcription factors in human islet cells remained unclear. Here, we present the NKX6.1-positive ratio of glucagon-positive cells (NKX6.1+/GCG+ ratio) and the ARX-negative ratio of glucagon-positive cells (ARX−/GCG+ ratio) in 34 patients who were not administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…We again see that many of the important genes predicted by our method using the consensus importance score ( Fig. 4c ) play a key role in pancreas development ( Table 2 ) ( Liu et al 2011 , Muraro et al 2016 , Byrnes et al 2018 , Millership et al 2018 , Sakata et al 2019 , Fujita et al 2021 , Bosi et al 2022 ). Moreover, we observe substantial enrichment of pathways and cellular components specific to pancreas-related functions within the gene sets associated with each cell type.…”
Section: Resultsmentioning
confidence: 65%
“…We again see that many of the important genes predicted by our method using the consensus importance score ( Fig. 4c ) play a key role in pancreas development ( Table 2 ) ( Liu et al 2011 , Muraro et al 2016 , Byrnes et al 2018 , Millership et al 2018 , Sakata et al 2019 , Fujita et al 2021 , Bosi et al 2022 ). Moreover, we observe substantial enrichment of pathways and cellular components specific to pancreas-related functions within the gene sets associated with each cell type.…”
Section: Resultsmentioning
confidence: 65%
“…4d,e). We again see that many of the important genes predicted by our method play a key role in pancreas development (Table 2) (30)(31)(32)(33)(34)(35)(36) and strong pathway and cellular component enrichment in the genes for each cell type related to pancreas functions (regulating cell secretion, hormone activity, hormone transport, and pancreas development). Table 1.…”
Section: Using Adversarial Training Can Discover Key Genes and Pathwa...mentioning
confidence: 73%
“…The Ki-67 index was <2% (data not shown) and was thus classified as neuroendocrine tumor (NET) G1 (23). Immunohistochemical studies using an indirect immunofluorescence method (24) showed that most tu-mor cells were positive for both insulin and calcitonin immunoreactivity (Fig. 2) but negative for glucagon and somatostatin immunoreactivity (data not shown).…”
Section: Case Reportmentioning
confidence: 98%